THE DEVELOPMENT OF MODEL ACCESS FOR EMERGENCY MEDICAL SERVICES IN STROKE PATIENTS BY NETWORKS, KANTHARALAK DISTRICT, SISAKET PROVINCE - ไกรยา บุญน้อม; ศิระรัตนาวัฒน์ นิญาพัชญ์; แซ่เตีย ยุพาวดี (Primary Health Care Journal (Northeastern Edition), 2023)
This research and development objective is to study and develop a model for accessing the emergency medical service system for stroke patients through by network. Kantharalak District, Sisaket Province. The study was divided into 3 phases as follows: Phase 1 studied factors related to access to the emergency medical service system. The sample group is Patients in the group at risk for cardiovascular disease, totaling 65 people. Data was collected by questionnaire. Data were analyzed using descriptive statistics. Phase 2: Develop a model for accessing the emergency medical service system for stroke patients. The information is a community network of 70 people involved in access to emergency medical services for stroke patients. Data were collected by in-depth interviews and workshop recordings. Data were analyzed by content categorization and content analysis, and Phase 3 evaluated the use of the emergency medical service system access model for stroke patients, by applying the model to 40 patients with chronic diseases, who are at risk for stroke. Data were analyzed using inferential statistics, including Paired t-test. The research results found that Most of the sample had a moderate level of knowledge about stroke, 73.8%, knowledge about the emergency medical service system was at a high level, 69.2 percent, attitudes about emergency medical services were at a fair level, 84.6%, and beliefs about emergency medical services were at a fair level, 50.8%. The Model for accessing the emergency medical service system for stroke patients by the network is the KTL C2NFS Model. After using the model was found that the average score of knowledge about stroke, Knowledge of emergency medical service systems, Attitudes about the emergency medical service system and Beliefs about the emergency medical service system was higher than before the experiment, statistically significant at the .05 level (p-value < .001). The developed model can increase the efficiency of access to the emergency medical service system for stroke patients by the network according to the set goals.